2002
DOI: 10.1046/j.1365-3024.2002.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salivary gland extracts from the tick, Boophilus microplus, on leucocytes from Brahman and Hereford cattle

Abstract: The effect of salivary gland extract (SGE) from Boophilus microplus on peripheral blood lymphocytes, neutrophils and monocytes from Brahman (Bos indicus) and Hereford (Bos taurus) cattle was investigated. SGE (8 micro g) significantly inhibited the proliferation response of lymphocytes to concanavalin A from both Brahman and Hereford cattle by 89% and 41%, respectively. The difference in inhibition between the two breeds was highly significant (P < 0.01), whilst at 1 micro g of SGE, significant inhibition of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…No proliferation was detected above background levels from PBMC stimulated with tick antigen extracts in vitro in either breed. This result could be due to an inhibitory action of the tick antigen extracts, as previously reported by Turni et al (42), who showed that addition of tick SGEs could inhibit the proliferative response of cells from B. taurus and B. indicus animals to ConA stimulation. The extracts of whole adult female ticks used in the present study may have contained sufficient quantities of SGEs (and other proteins) capable of causing inhibition.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…No proliferation was detected above background levels from PBMC stimulated with tick antigen extracts in vitro in either breed. This result could be due to an inhibitory action of the tick antigen extracts, as previously reported by Turni et al (42), who showed that addition of tick SGEs could inhibit the proliferative response of cells from B. taurus and B. indicus animals to ConA stimulation. The extracts of whole adult female ticks used in the present study may have contained sufficient quantities of SGEs (and other proteins) capable of causing inhibition.…”
Section: Discussionsupporting
confidence: 74%
“…The proliferative response of bovine peripheral blood mononuclear cells (PBMC) to stimulation with the T-lymphocyte mitogen phytohemagglutinin (PHA) was inhibited by the addition of salivary gland protein to the culture (17), and subsequent studies showed that sufficient prostaglandin E 2 is present in tick saliva to be responsible for this inhibition (16). Turni et al (42) found that low concentrations of R. microplus salivary gland extract (SGE) inhibited the oxidative burst capacity of monocytes and neutrophils, as well as the proliferation response of PBMC to concanavalin A (ConA) in vitro, in both B. taurus and B. indicus cattle. However, a higher concentration of SGE caused a significant difference in the degree of inhibition observed in the proliferation assay between the B. taurus and B. indicus cells: a 40.7% and an 88.5% reduction, respectively.…”
mentioning
confidence: 99%
“…Differences between Zebu (B. taurus indicus) and European (B. taurus taurus) cattle in terms of natural resistance to diseases have also been reported (Martínez et al, 2010;Macêdo, 2012); however, whether these cattle differ in their peripheral blood leukocyte profiles is unclear, although this may account for the more efficient immunity observed in some breeds. Importantly, some evidence suggests that peripheral blood leukocytes from Zebu may respond differently than cells from European breeds when stimulated (Turni et al, 2002). Furthermore, clear differences have been observed in the frequency of alleles of Nramp1, a gene that has been linked to natural resistance to intracellular pathogens (Paixão et al, 2006(Paixão et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in-vitro proliferative responses of mouse, human, or cattle lymphocytes to SGE of partially engorged female ticks were found to be suppressed (Bergman et al 1995, Schoeler et al 2000, Kovář et al 2001, Turni et al 2002, however, no data have been available on the effects of SGE derived from unfed female or male ixodid ticks. Sexual behaviour of some tick species evokes speculation about possible cooperation between sexes in the interaction with the host (Bior et al 2002).…”
Section: Amblyomma Variegatum -Femalesmentioning
confidence: 99%